The demands of cultural-missionary communication in the media - Tănăsescu, Eugen (Technium Social Sciences Journal, 2023)
The phenomenon of media communication constitutes one of the essential characteristics of society. Without communication, society could not function. The Church cannot avoid the use of means of communication, for the simple reason that its mission is masterfully described by St. Apostle Paul who says: ". . . I have become all things to all, that I may save some." (1 Cor 9, 22). Therefore, an essential aspect of media communication in the Church is to make ourselves understood by the audience as well as possible. In this context, we will analyze what are the demands of cultural-missionary communication, so that the cultural and missionary values of the Church fulfill the meaning of their existence.